On the Cholesky decomposition for electron propagator methods: general aspects and application on C60 - Vysotskiy, Victor P.; Cederbaum, Lorenz S. (The journal of chemical physics, 2010)
To treat the electronic structure of large molecules by electron propagator methods we developed a parallel computer program called P-RICDΣ. The program exploits the sparsity of the two-electron integral matrix by using Cholesky decomposition techniques. The advantage of these techniques is that the error introduced is controlled only by one parameter, which can be chosen as small as needed. We verify the tolerance of electron propagator methods to the Cholesky decomposition threshold and demonstrate the power of the P-RICDΣ program for a representative example (C60). All decomposition schemes addressed in literature are investigated. Even with moderate thresholds the maximal error encountered in the calculated electron affinities and ionization potentials amount to a few meV only, and the error becomes negligible for small thresholds.
Im Titel erscheint die Zahl 60 tiefgestellt
Gesehen am 19.09.2023